From Competency Assessment to Curriculum Reform: How Does Artificial Intelligence Empower Higher Vocational Education? - Wang, Sufen; Xu, Mengqi (Journal of Theory and Practice in Education and Innovation, 2025)
This study explores the impact of Artificial Intelligence (AI) on vocational education, focusing on its role in competency assessment and curriculum reform. With the rapid evolution of technology, AI is poised to revolutionize how vocational training is delivered and assessed. By utilizing a quantitative research approach, a survey was conducted with 100 vocational students currently engaged in AI-integrated training. The findings reveal that while AI-based training provides personalized learning experiences, its direct impact on competency assessment was less significant than expected. In contrast, student engagement emerged as a critical factor influencing the effectiveness of AI in enhancing learning outcomes.